Prognostic Factor Analysis and Nomogram Construction of Primary Retroperitoneal Liposarcoma: A Review of 10 Years of Treatment Experience in a Single Asian Cohort of 211 Cases - Zhuang, Aobo; Zhuang, Aojia; Wu, Qian; Lu, Weiqi; Tong, Hanxing; Zhang, Yong (Frontiers in Oncology, 2022)
Objective This study intended to retrospectively analyze the data of patients with primary retroperitoneal liposarcoma in a single Asian large-volume sarcoma center, and to establish nomograms focused on PRLPS for predicting progression-free survival (PFS) and overall survival (OS). Methods 211 patients treated surgically for primary, non-metastatic retroperitoneal liposarcoma during 2009–2021 were identified and clinicopathologic variables were analyzed. PFS and OS nomograms were built based on variables selected by multivariable analysis. The discriminative and predictive ability of the nomogram were assessed by concordance index and calibration curve. Results The median follow-up time was 25 months. 117 (56%) were well-differentiated, 78 (37%) were dedifferentiated, 13 (6%) were myxoid, and 3 (1%) were pleomorphic morphology. Compared to the western population cohort reported by the Memorial Sloan-Kettering Cancer Center, the median age of patients in this cohort was younger (57 years vs. 63 years), the tumor burden was lower (20 cm vs. 26 cm) and the proportion of patients with R0 or R1 resection was higher (97% vs. 81%). Five-year PFS rate was 49%, and factors independently associated with PFS were symptoms at visit, preoperative needle biopsy, histologic subtypes, and postoperative hospital stay. Five-year OS rate was 72%. American Society of Anesthesiologists Physical Status and Clavien-Dindo classification were independently associated with OS. The concordance index for PFS and OS nomograms were 0.702 and 0.757, respectively. The calibration plots were excellent. Conclusions The proposed nomogram can provided a favorable reference for the treatment of primary retroperitoneal liposarcoma patients.